Effect Of Pictorial Riddle Learning Method On Understanding Physical Concept Of Students Of Smp Negeri 2 Painan - Syaflir Syaflir (Fakultas Sastra Universitas Ekasakti, 2017)
The result of observation shows that the students' understanding of physics science subject is still low. Many teachers still use conventional methods. Students just listen and take notes. Therefore, the use of appropriate and varied learning models is expected to help students in understanding a concept. One alternative of physics learning that can help students understand the concept is through pictorial riddle learning method. This pictorial riddle learning method uses a riddle of drawings on a whiteboard, poster or projected from a transparency then the teacher asks questions relating to the riddle. The purpose of this study is to determine the extent of the influence of pictorial riddle learning method on the understanding of physics concepts class IX students semester 1 SMP Negeri 2 Painan 2015/2016 academic year. Sampling is done by simple random sampling technique. The research population is all students of class IX SMP Negeri 2 Painan. The sample used is class IX-2 as experiment class and IX-3 as control class. The variable in this research is the students' concept understanding on the magnetism materials, with the experimental control group design pre test post test. Data retrieval is done through the test in the form of free description and analyzed using simple regression analysis, coefficient of determination and test of significance in microsoft excel. The results of data analysis showed the relationship between variables expressed in a simple regression equation Y = 51.99 + 0.4286. The value of correlation coefficient 0,5787 with enough criterion (0,5 <r <0,8) value 0,3348 and coefficient of determination equal to 33,5% and> (3,175> 2,015) at significance level 5%, which mean study pictorial Riddle method effect of 33.5% on the understanding of student physics concepts. Thus it can be concluded that there is a positive influence and quite significant method of learning pictorial riddle on the understanding of students' concepts on magnetism materials.